High Yielding Corn Production with Subsurface Drip Irrigation - F. R. Lamm (Kansas Agricultural Experiment Station Research Reports, 2022)
This corn intensification study was conducted under subsurface drip irrigation (SDI) from 2017 to 2021 at the Kansas State University Northwest Research-Extension Center near Colby, KS. Two corn hybrids (Pioneer 1151 and Pioneer 11197) were grown with advanced fertilization at three plant densities (42,000, 38,000, and 34,000 plants/a) using three irrigation levels (115, 100, or 85% of calculated well-watered ET minus rain). Average yields were 259, 257, and 254 bu/a for the 115, 100, and 85% ET - Rain irrigation levels respectively, indicating that irrigation does not have to increase with crop intensification when using SDI. Both corn hybrids yielded well, and plant densities that were greater than 34,000 plants/a attained slightly greater yields.
Keywords: crop intensification; irrigated corn; drip irrigation; water productivity